Consolidating skill learning through sleep. (April 2018) - Nusbaum, Howard C; Uddin, Sophia; Van Hedger, Stephen C; Heald, Shannon LM
Highlights: We review current research on how sleep benefits skill learning by consolidating memory. Sleep restores memories from learning a skill that are lost through interference. Sleep protects memories from learning a skill against future forgetting from interference. Sleep consolidation of learning may reorganize memories in order to stabilize memory. Sleep promotes the generalization and abstraction needed for effective skill learning. Abstract : Skill learning depends on retaining memories of skill-use experiences over time. These memories need to be robust against interference and therefore depend on consolidation. Further, skills must generalize beyond the learning experiences to be useful in novel but related situations. We review the role of sleep in the consolidation of skill learning, along with research findings that sleep: (1) reduces the effects of interference on skill learning, (2) protects against future interference with skill learning, (3) aids in the abstraction and generalization of skill learning. We discuss theories of sleep consolidation in terms of putative neural mechanisms and describe the key paradigms and questions in sleep research.